Atraucan®: A New Needle for Spinal Anesthesia. Issue 4 (July 1993) - Scott, Bruce D.; Dittmann, Martin; Clough, David G. F.; Van Steenberge, Albert; Morrison, Lachlan M. M.; Van Zundert, Andre; Joos, Stephane S.; Eisenach, James C.
Abstract : Background and Objectives: Atraucan ® 26-gauge spinal needles have a tip designed to make a small linear cut (as opposed to a V-shaped cut) in the dura mater. The cut is shorter than the outside diameter of the needle and is dilated as the needle passes through the dura. The needle is used with a 20-gauge introducer. In vitro, it causes less leakage of cerebrospinal fluid than Quincke 26-gauge or Sprotte 24-gauge needles. This study was designed to test the ease of use and any damage caused to the needle tip during lumbar dural puncture. Methods: This was a multicenter trial (six centers in five countries) involving 362 patients undergoing spinal anesthesia. A detailed questionnaire was filled in for every patient by the anesthesiologist. All the needles were returned to the factory and examined microscopically for damage. Results: Lumbar dural puncture was successful in all but one patient. Spinal anesthesia was satisfactory for the planned surgery in 97%. Microscopy of the needle tips showed only a minor degree (0.01-0.19 mm) of bending in 14%, and none of the tips had a "hook." Postdural puncture headache (PDPH) occurred in nine patients (2.5%), all but one of whom (a 15-year-old male) were females under 55 years of age. Conclusions: The Atraucan ® needle is easy to use and has a high success rate in identifying the subarachnoid space. Lumbar dural puncture causes minimal damage to the tip. The incidence of PDPH is low, but a larger comparative study needs to be performed.